Multiloop Parallelisation Using Unrolling and Fission - Yuet Ming Lam; José Gabriel F. Coutinho; Chun Hok Ho; Philip Heng Wai Leong; Wayne Luk (International Journal of Reconfigurable Computing)
A technique for parallelising multiple loops in a heterogeneous computing system is presented. Loops are first unrolled and then broken up into multiple tasks which are mapped to reconfigurable hardware. A performance-driven optimisation is applied to find the best unrolling factor for each loop under hardware size constraints. The approach is demonstrated using three applications: speech recognition, image processing, and the N-Body problem. Experimental results show that a maximum speedup of 34 is achieved on a 274 MHz FPGA for the N-Body over a 2.6 GHz microprocessor, which is 4.1 times higher than that of an approach without unrolling.